Research progress on assessment tools related to occupational fatigue in nurses: a traditional review - Zeng, Zhi; Zhou, Sumei; Liu, Meng (Frontiers in Public Health, 2024)
Nurse occupational fatigue is a significant factor affecting nursing quality and medical safety. Scientific and effective assessment of occupational fatigue is beneficial for strengthening nurse occupational health management, improving the quality of life for nurses, and ensuring patient safety. This article provides a narrative review of the content, reliability, validity, characteristics, application status, and advantages and disadvantages of assessment tools related to nurse occupational fatigue. These tools include single-dimensional assessment scales (Fatigue Severity Scale, Chinese version of Li Fatigue Scale), multidimensional assessment scales (Fatigue Scale-14, Fatigue Assessment Scale, Multidimensional Fatigue Scale, etc.), and other assessment tools. Our review reveals limitations in existing occupational fatigue assessment tools, such as variability in accuracy and applicability across different populations, and potential biases. These findings underscore the critical role of these tools in nursing management and occupational health, advocating for continuous refinement and innovation. Future research should focus on developing more comprehensive, context-specific tools to address the multifaceted nature of nurse occupational fatigue. Nursing managers must carefully select appropriate tools to effectively identify and mitigate fatigue, thereby enhancing nurse well-being and patient care quality.